Investigating variables affecting heap (bio)leaching through determining access to sub-surface mineral grains by micro-scale X-ray tomography - Ghadiri, Mahdi (Centre for Bioprocess Engineering Research, 2020)
Heap bioleaching is a hydrometallurgical technology, used to facilitate the extraction of valuable metals such as copper, gold, nickel and uranium from low-grade, typically sulphidic, ores. The process is highly complex as it is influenced by interactions of different sub-processes including flow of leaching solution around the ore particles, mass and heat transfer within and around the particles, chemical reactions, microbially-mediated reactions and microbial growth. Contact of leaching solution with mineral grains is necessary for oxidation of the sulphide minerals. However, a large fraction of the mineral grains is positioned below the surface of the ore particles and so contact with the liquid occurs through cracks and pores in the ore connected to the surface. Long extraction times and low metal recoveries typical of heap systems can be attributed to the slow leaching rate of these non-surface mineral grains as well as constraints on their accessibility. Most of the valuable grains that remain in the residue ores are non-surface grains. Therefore, investigation of the mechanism and behaviour of non-surface grain leaching and quantification of the factors contributing to their leaching is expected to be highly beneficial in the optimisation of leach conditions and recoveries. Non-surface grain leaching within large particles cannot be investigated via traditional experimental methods reliant on bulk measurements, 2D or destructive methodologies. However, it can be studied using high resolution, non-destructive 3D X-ray micro-Computed Tomography (μCT), an imaging technique for investigation of internal structure of opaque objects. X-ray μCT has previously been developed and used for investigation of different aspects of heap leaching. In the current study, the viability of using X-ray μCT to study heap bioleaching systems and affecting variables is assessed. This required establishment of procedures for measurement and analysis of sulphide and oxide mineral recoveries and leaching penetration distances. The feasibility of studying biotic heap leaching by X-ray μCT was explored through investigation of the relative energies required for high mineral resolution and avoidance of microbial inactivation. Specific bioleaching operating variables that were subsequently considered included: the accuracy and representivity of the X-ray μCT images, the influence of agglomeration pre-treatment, operating temperature, and type of ore on non-surface grain leaching. Addition of surfactants to the leaching solution was explored with the aim of changing surface activity to influence the penetration of the leach agent into pores and cracks in the ore. The effects of operating conditions on non-surface mineral grain leaching was studied using mini-column experiments. Three different low-grade ores, namely a chalcopyrite-rich ore, a malachite ore and a waste rock containing pyrite were prepared for the leaching experiment. The ores were crushed using a jaw crusher and comminuted down to 100% passing 16 mm. The products were sieved into six fractions (<0.25 mm, 0.25 - 1 mm, 1 - 2 mm, 2 - 5.6 mm, 5.6 - 8 mm, 8 - 16 mm) and each fraction then representatively split into smaller portions using a rotary splitter. One portion of each size fraction was taken for XRD, AAS and QEMSCAN analyses. Mini leaching columns were designed and constructed based on the target mineral grain distribution in the ores to ensure that the mineral grains were detectable using X-ray µCT, given its resolution limitations. The columns were charged with 50 g of agglomerated or non-agglomerated ore and lixiviant was provided at a flow rate of 2.55 mL h -1 for a period of 5.5 months for chalcopyrite and pyrite and 26 days for malachite in incubators at 30 °C, 37 °C and 65 °C. In order to select a surfactant suitable for use in a biological leach experiment, the effect of five different types and concentration of non-ionic surfactants on bioleaching microorganisms was studied in terms of microbial growth, ability for ferrous ion oxidation and chalcopyrite bioleaching. This was done in shake flask experiments using mineral concentrate. Based on the results of these experiments, Tween® 20 (10 mg L -1 ) was selected to study the effect of surfactant on non-surface mineral grain leaching in the mini-columns. Each column was scanned by X-ray μCT at 100 kV and 150 mA using a 0.38 mm copper filter and at a distance of 59.40 mm between X-ray gun and specimen. The advanced 3D analysis software Avizo® 9 was used to visualize and analyse image data. The Interactive Thresholding function in Avizo® 9 software was used for segmentation of ore particles from air and sulphide minerals from air and gangue minerals, to measure the target minerals' volume reduction during leaching. The Distance Map Algorithm was applied on a binary (segmented) image to calculate the distance of the sulphide mineral from the ore particle surface. Imaging of the whole mini-column was done before leaching and at the end of each experiment and imaging of certain sections was done at select time points during leaching to track temporal leaching dynamics. Good agreement was seen between the bulk mineral recovery data, determined using standard chemical assays, and the leaching curves generated using the X-ray µCT images for all the ores, confirming that the X-ray µCT images were a good quantitative measurement of the sulphide and oxide mineral leaching. Liquid microbial culture experiments were used to confirm that exposure to X-ray does not affect microbial activity for energy doses between 35 and 90 kV at 200-280 μA. However, X-ray exposure was found to have a slight negative influence at higher voltages of 120 and 150 kV, temporarily reducing the specific ferrous ion oxidation and suppressing the specific growth rate of the bioleaching microorganisms. The X-ray exposure thus negatively affected both the total microbial population available for leaching (population viability) as well as the metabolic activity of the individual microorganisms (population vitality). The effect of X-ray exposure on bioleaching cultures attached to a mineral surface was examined using pyrite-coated glass beads packed into mini-columns. The energy dosage limits identified in the liquid culture experiments were found to be compatible with the X-ray μCT imaging conditions (minimum energy dosage and sample position) required for acquisition of complete and accurate images of the columns at a resolution that allows identification of individual mineral grains. Following X-ray exposure, the performance of the exposed bioleaching mini-columns was equivalent to the unexposed control column. Similarly, the microbial activity and presence on the mineral surface appeared unchanged. Finally, the experiment was performed on the chalcopyrite ore and the microorganisms were found to still be able to convert Fe2+ to Fe3+ after 2 scanning runs. Thus, all sets of results confirm that X-ray μCT can be compatible with heap bioleaching experiments, while still permitting appropriate resolution of the mineral grains to make an X-ray μCT investigation worthwhile. However, cognisance that an upper limit of tolerable X-ray exposure exists must be taken. This may present a challenge if it is desired to image larger or denser ore samples which require a greater X-ray energy level for sufficient penetration of the sample by the X-rays and hence accurate imaging. In chalcopyrite leaching, increasing temperature from 37 °C to 65 °C resulted in clear enhancement of leaching based on both analysis methods, with the copper recovery increasing from 20% to 64% by the end of the leaching period, and the overall sulphide mineral dissolution increasing from 24% to 67%. Increasing temperature from 37 °C to 65 °C resulted in an increased leaching penetration distance and crack development in the particles, and thus an enhancement in copper recovery and sulphide mineral dissolution. This was in addition to the thermodynamically expected increased leaching rate. The maximum leaching penetration distance, beyond which no mineral volume change is observed, at 37 °C was 1.7 mm. This increased to 2.5 mm at 65 °C. As a result of addition of 10 mg L-1 Tween® 20 into the leaching solution, the final copper recovery was improved by 4% to 68% and the maximum penetration distance increased to 2.9 mm. However, when the availability of sulphide mineral was not rate limiting, the copper recovery and sulphide mineral volume reduction in the mini-column with surfactant was lower than the system without surfactant. This may have been due to depression of diffusion of ferric ion to the ore surface as a result of the formation of an adsorbed surfactant layer on the mineral surface. The performance with surfactant became superior as the amount of readily leachable mineral became limiting. In the pyrite waste rock, an increase in temperature did not have any effect on the maximum penetration distance and any increase in iron recovery was only for thermodynamic reasons. Similarly to the chalcopyrite ore, during the later period of leaching when readily exposed mineral grains have been depleted, the system performed better in the presence of surfactant. The addition of surfactant increased the maximum penetration distance from 2.7 to 2.9 mm. The cumulative copper recovery of 86% was obtained for malachite ore in 26 days of acid leaching and the maximum penetration distance was 2.2 mm. This study thus demonstrates the value of the X-ray µCT technique for quantitative investigation of non-surface mineral grain leaching and confirms that the maximum penetration distance can be affected with changing operation conditions or ore type. This study thus demonstrates the X-ray µCT technique for quantitative investigation of non-surface mineral grain bioleaching and confirms that the maximum penetration distance can be affected with changing operation conditions. Critically, the results confirm that X-ray μCT can be compatible with bioleaching microorganisms, while still permitting appropriate resolution of the mineral grains to make an X-ray μCT investigation worthwhile.